Cooperative opportunistic network-coded transmission strategy for wireless mesh networks. (2015) - Xiong, Ke; Fan, Pingyi; Yi, Su; Lei, Ming; Zhong, Zhangdui
This paper considers a wireless mesh network model, where two sources want to transmit their information to their own destination, respectively, via the help of a common relay node. In order to improve the network performance by taking the advantage of opportunistic network coding (ONC), automatic repeat request (ARQ) and cooperative diversity, we propose a new cooperative opportunistic network-coded transmission strategy (CP-ONC), which employs truncated ARQ and cooperative diversity to enhance the reliability of the wireless links so that more network coding opportunities can be obtained in CP-ONC. Both network throughput and delay are theoretically analysed, where we derive some explicit expressions for them. Extensive simulations show that our proposed CP-ONC achieves much higher network throughput and lower delay than ONC, especially in low signal to noise ratio (SNR) region. Besides, we also discuss the impact of the system configuration parameters and network topology on system performances.